2021
DOI: 10.3390/polym13152517
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glycero-(9,10-trioxolane)-trialeate on the Physicochemical Properties of Non-Woven Polylactic Acid Fiber Materials

Abstract: Biocompatible glycero (9,10-trioxolane) trioleate (ozonide of oleic acid triglyceride, OTOA) was incorporated into polylactic acid (PLA) fibers by electrospinning and nonwoven PLA mats with 1%, 3% and 5% OTOA content. The morphological, mechanical, thermal and water sorption properties of electrospun PLA mats after the addition of OTOA were studied. A morphological analysis showed that the addition of OTOA increased the average fiber diameter and induced the formation of pores on the fiber surface, leading to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 58 publications
(86 reference statements)
2
6
0
Order By: Relevance
“…To obtain film materials, NatureWorks ® Ingeo™ 3801X Injection Grade PLA (SONGHAN Plastics Technology Co., Ltd., Shanghai, China) with a viscosity-average molecular weight of 1.9 × 10 5 g/mol was used; PCL was used (SONGHAN Plastics Technology Co., Ltd., Shanghai, China) with a molecular weight of 90,000 ( Figure 1 ). Solutions were prepared using ≥99.5% dry purified chloroform (Sigma-Aldrich Inc., St. Louis, MO, USA); Glycero-(9,10-trioxolane)-trioleate (oleic acid triglyceride ozonide (OTOA)) was provided by Medozon (Moscow, Russia), and its chemical structure was described previously [ 17 , 18 ]. All reagents were used as received.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain film materials, NatureWorks ® Ingeo™ 3801X Injection Grade PLA (SONGHAN Plastics Technology Co., Ltd., Shanghai, China) with a viscosity-average molecular weight of 1.9 × 10 5 g/mol was used; PCL was used (SONGHAN Plastics Technology Co., Ltd., Shanghai, China) with a molecular weight of 90,000 ( Figure 1 ). Solutions were prepared using ≥99.5% dry purified chloroform (Sigma-Aldrich Inc., St. Louis, MO, USA); Glycero-(9,10-trioxolane)-trioleate (oleic acid triglyceride ozonide (OTOA)) was provided by Medozon (Moscow, Russia), and its chemical structure was described previously [ 17 , 18 ]. All reagents were used as received.…”
Section: Methodsmentioning
confidence: 99%
“…OTOA is non-toxic, biocompatible, has good biodegradability and antimicrobial activity. In recent studies [ 17 , 18 ], it has been already shown that the introduction of OTOA into PLA fibers and films led to improvement in the physicochemical properties of the material. We have now obtained novel film materials based on a PLA/PCL blend with the addition of various amounts of OTOA (0–40 wt %) as a modifier.…”
Section: Introductionmentioning
confidence: 99%
“…For example, when ozonizing vegetable oils, ozone reacts with unsaturated triacylglycerols contained in them (Figure 2) [28]. The oil ozonation product is a nontoxic, biocompatible, and biodegradable material, and is also a promising additive for introduction into the fibrillar matrix through electrospinning [29]. Combining the plasticizing properties of ozone-modified germicidal oils and the specificity of electroformed materials, it is possible to obtain a fundamentally new product with improved characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The authors [29] succeeded in introducing the oil ozonation product, glycerol (9,10-trioxolane) trioleate (ozonide of oleic acid triglyceride (OTOA)), into the electrospinning polymer matrix to obtain highly porous medical fibers. Fundamentally, new non-woven mats based on PLA with the addition of OTOA (1, 3, and 5 wt.…”
Section: Introduction Of Ozonated Oils Directly Into the Non-woven Fibermentioning
confidence: 99%
See 1 more Smart Citation